2018
DOI: 10.29333/ejmste/90994
|View full text |Cite
|
Sign up to set email alerts
|

Creativity of Pre-service Teachers in Problem Posing

Abstract: Problem posing and technology are attracting the attention of mathematics educators because of their potential to affect positively many aspects of students' learning. Little research has been done on the relationship between technology and mathematical creativity. The present study investigates this issue in the context of problem posing, in the presence and absence of a strategy for problem posing (the "what-if-not" strategy). Participants were pre-service mathematics teachers. The research was conducted dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
1
15
0
2
Order By: Relevance
“…On the other hand, the particular processes imply that there is room for the individual student to be different in his or her creativity in mathematical problem solving, which gives more space for creativity. The encouragement of creativity processes could happen when using open-ended problems (Daher & Anabousy, 2018a), as halving-the-rectangle described in the present research.…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, the particular processes imply that there is room for the individual student to be different in his or her creativity in mathematical problem solving, which gives more space for creativity. The encouragement of creativity processes could happen when using open-ended problems (Daher & Anabousy, 2018a), as halving-the-rectangle described in the present research.…”
Section: Discussionmentioning
confidence: 68%
“…"I do the task faster and do more than other children" Fluency indicators in the ability to think creatively are related to the number of ideas or answers produced by students. Fluency in creative thinking can be seen from the number of problems given and given answers to the problem [50][51][52][53][54]; which will later involve students actively to carry out activities to explore problems to develop various problem-solving ideas. That makes this research work with Fluency indicated by the ability to produce a large number of ideas to solve problems smoothly and precisely and find different and extraordinary ideas to solve a problem [55].…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
“…During learning, not all groups are able to provide more than one varied strategy. But this deficiency can be supplemented by group discussions because there is an opportunity for groups with different strategies to express their opinions so that various strategies emerge which can later present a concept in different ways that show student creativity [54][55][56][57][58][59].…”
Section: Flexibilitymentioning
confidence: 99%
“…Tools and strategies are suggested as means that empower students in their mathematics problem solving activity. Two such tools and strategies are technology (e.g., [1,2]), especially programming (e.g., [3]), and meta-cognition (e.g., [4][5][6]). For tools and strategies to be effective in processes of teaching and learning, an expert teacher is needed, which indicates the need for prospective teachers' preparation in the utilization of tools and strategies in the classroom processes.…”
Section: Introductionmentioning
confidence: 99%